(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Balanced environment Elderly folks are defined as those who have maintained their riches and raised their social status. Joint soreness has been linked to a negative quality of life for up to 64% of senior persons in partner sites. Furthermore, just 47% of elderly adults are familiar with methods for reducing joint discomfort. As a result, community service initiatives are implemented to reduce pain and enhance mobility and functional capacities in order to improve the quality of life for senior citizens. The participative action research methodology is used with the participatory rural appraisal approach. Activity stages include preparation, execution (training on joint pain reduction and exercise training to increase older people’s mobility and function), mentorship, and cadreship. Including senior Posyandu Pelangi Nusantara cadres, 49 senior persons took part in this event. The community service program has the potential to enhance the older population’s comprehension of joint discomfort relief; at present, 82% of the seniors possess proficiency in this domain. A Furthermore, from 85% to 60% fewer older persons reported having mild to moderate discomfort. Thus, the following dimensions impact the high quality of life that the elderly experience: psychological (57.12%), social relationships (63.3%), environment (75.5%), and health (61.2%).